Cutaneous and systemic mycoses from infection with Lecanicillium spp. in captive Guthega skinks (Liopholis guthega). Issue 7 (July 2015) - Scheelings, TF; Dobson, EC; Hooper, C; Eden, P
<x xml:space="preserve">Abstract</x> Background Guthega skinks have been listed as critically endangered and are considered particularly vulnerable to extinction because of their isolation and restricted distribution. There is no information on their captive husbandry, or the diseases that affect them. Case report Cutaneous and systemic mycosis from infection with Lecanicillium spp. was diagnosed in a captive colony of Guthega skinks (Liopholis guthega). Infection resulted in the death of five lizards. Diagnosis of infection was confirmed using a combination of histopathology, fungal culture and DNA sequencing from all affected animals. An additional four similarly affected individuals were successfully treated with a combination of voriconazole (10 mg/kg PO once daily) and shallow baths of benzalkonium chloride and polyhexamethylene biguanide hydrochloride (F10) (1 : 250, 20 min once daily). This is the first report of Lecanicillium spp. infection in reptiles.